Estimating Parking Utilization in Multifamily Residential Buildings in Washington, D.C. Issue 1 (2016) - Rogers, Jonathan; Emerine, Dan; Haas, Peter; Jackson, David; Kauffmann, Peter; Rybeck, Rick; Westrom, Ryan
The District of Columbia's Department of Transportation and Office of Planning recently led a research effort to understand how parking utilization in multifamily residential buildings is related to neighborhood and building characteristics. Prior research has shown that the overbuilding of residential parking leads to increased automobile ownership, vehicle miles traveled, and congestion. Parking availability can affect travel mode choices and decrease the use of transportation alternatives. In addition, zoning regulations requiring supplies of parking that exceed demand can increase housing costs and inhibit the development of mixed-use, mixed-income, pedestrian-friendly neighborhoods. The primary research goal was to develop an empirical model for parking utilization in Washington, D.C., and to apply the model to an interactive web-based tool, named ParkRight DC, to support and guide parking supply decisions. A transparent, data-driven process for parking supply decisions may help relieve problems associated with over- or undersupply of parking. This paper outlines the data collection, model-development process, functionality of the resulting tool, and findings on key relationships and policy implications. The model and the associated tool rely on local information reflecting residential development and automobile ownership patterns drawn from a survey of multifamily residential parking use at 115 buildings covering approximately 20, 000 dwelling units in the District of Columbia. The resulting model achieved an R 2 -value of .835, which indicates a strong model, given the complexity of the relationship being researched.